Students’ difficulties on writing undergraduate thesis at Islamic university - Fanesa Maura Aprillia; Edi Rozal; Aryawira Pratama (Journal of Research on English and Language Learning (J-REaLL), 2023)
Until now, there are still students who do not graduate on time. This study aims to determine the difficulties of students in writing undergraduate thesis in the English Tadris Study Program, UIN Sulthan Thaha Saifuddin Jambi. Researcher used case study designs and 31 questions interviews as research instruments. This research was conducted at the English Education Study Program, UIN Sulthan Thaha Saifuddin Jambi. The subjects in this study were 5 female and 5 male who were selected using a purposive sampling technique based on several criteria. In this study, the researcher found that there were some difficulties for students in writing their thesis. These difficulties include: difficulties regarding basic knowledge of thesis; Psychological; Economic; Socio-Cultural; The consultation process with the advisor; and Technological. Besides that, researchers also found other results, which are students' difficulties in lacking basic English knowledge and skills, academic requirements files, study programs and faculty academic services.